PENINGKATAN KESADARAN SISWA TERHADAP HIGIENE, ERGONOMI, DAN KEAMANAN SIBER MALALUI SOSIALISASI DI SEKOLAH-SEKOLAH KOTA BATAM - Wahyudi, Sendy; Ardiansyah, Rizky; Haekal Bayani , Ahda; Rahmatullah, Anurrafiq; Tilidia Devaga, Army; Nisa Safitri, Khoerun (ASOSIASI IDEBAHASA KEPRI, 2025)
The digital outreach activity conducted by students of Universitas Ibnu Sina Batam at several secondary schools aimed to raise students' awareness of the importance of maintaining a clean learning environment, creating ergonomic classroom spaces, and understanding digital security threats that may disrupt learning. The main issue addressed was the low level of student literacy regarding healthy living practices and the risks of digital fraud. Through a technology-based educational approach, students delivered material interactively using visual presentations and conducted live simulations to demonstrate how to identify harmful messages and protect personal information. The methods used included face-to-face counseling, participatory discussions, and practical exercises to recognize suspicious messages resembling online scams. The results showed that students became more aware of personal and environmental hygiene, understood the need for classroom layouts that support comfort and safety, and demonstrated increased vigilance against the risk of data theft via digital platforms. The activity also encouraged students to actively participate in discussions and share experiences related to hygiene and cybersecurity in the school environment. It can be concluded that an integrated educational approach combining hygiene, ergonomics, and digital safety effectively provides new understanding for students and fosters critical thinking and responsibility in maintaining a healthy and secure learning atmosphere.